Serpent, Suppressor of Hairless and U-shaped are crucial regulators of hedgehog niche expression and prohemocyte maintenance during Drosophila larval hematopoiesis - Tokusumi, Yumiko (Company of Biologists, 2010)
The lymph gland is a specialized organ for hematopoiesis, utilized during larval development in Drosophila. This tissue is composed of distinct cellular domains populated by blood cell progenitors (the medullary zone), niche cells that regulate the choice between progenitor quiescence and hemocyte differentiation [the posterior signaling center (PSC)], and mature blood cells of distinct lineages (the cortical zone). Cells of the PSC express the Hedgehog (Hh) signaling molecule, which instructs cells within the neighboring medullary zone to maintain a hematopoietic precursor state while preventing hemocyte differentiation. As a means to understand the regulatory mechanisms controlling Hh production, we characterized a PSC-active transcriptional enhancer that drives hh expression in supportive niche cells. Our findings indicate that a combination of positive and negative transcriptional inputs program the precise PSC expression of the instructive Hh signal. The GATA factor Serpent (Srp) is essential for hh activation in niche cells, whereas the Suppressor of Hairless [Su(H)] and U-shaped (Ush) transcriptional regulators prevent hh expression in blood cell progenitors and differentiated hemocytes. Furthermore, Srp function is required for the proper differentiation of niche cells. Phenotypic analyses also indicated that the normal activity of all three transcriptional regulators is essential for maintaining the progenitor population and preventing premature hemocyte differentiation. Together, these studies provide mechanistic insights into hh transcriptional regulation in hematopoietic progenitor niche cells, and demonstrate the requirement of the Srp, Su(H) and Ush proteins in the control of niche cell differentiation and blood cell precursor maintenance.